Análisis de la cadena de valor de los residuos plástico del cantón buena fe, provincia de los ríos, ecuador - Vera Mera, Yulissa Yelena (2024)
The management of plastic waste in Buena Fe, Ecuador, faces challenges due to the prevalence of Polyethylene Terephthalate (PET). The characterization of this waste reveals an urgent need to improve the value chain to mitigate its environmental impact by assessing the plastic waste value chain from its production process to its final disposal. The research aligns with the Sustainable Development Goals (SDGs), focusing on health and well-being, responsible production and consumption. A data collection methodology was implemented through surveys, interviews, and statistical analysis to assess the current management of this waste. Additionally, the Per Capita Plastic Production (PPP) was calculated for two weeks, during which Las Vegas generated the highest amount of plastic waste with 1,386 kg. Data analysis was conducted using specialized software such as SPSS and Infostat, and the management of plastic waste was diagnosed, identifying areas for improvement and proposing sustainable strategies for the Buena Fe canton. Surveys were conducted with 383 residents, and the analysis of the plastic waste value chain revealed deficiencies in management, separation, recycling, and final disposal. Furthermore, interviews were conducted with stakeholders related to the value chain, including the municipal government, recycling companies, and informal recyclers. In response to these findings, strategies are proposed to improve the management of plastic waste in the canton. These include awareness and environmental education programs, incentives to promote separation and recycling, improvements in collection and recycling infrastructure, and partnerships with companies and organizations. It is crucial to address the management of plastic waste comprehensively, involving the community, local authorities, and businesses, to promote sustainable practices and mitigate negative effects on the environment and public health.